The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s41614-017-0013-2
|View full text |Cite|
|
Sign up to set email alerts
|

The magnetic Rayleigh–Taylor instability in solar prominences

Abstract: The magnetic Rayleigh-Taylor instability is a fundamental instability of many astrophysical systems, and recent observations are consistent with this instability developing in solar prominences. Prominences are cool, dense clouds of plasma that form in the solar corona that display a wide range of dynamics of a multitude of spatial and temporal scales, and two different phenomena that have been discovered to occur in prominences can be understood as resulting from the Rayleigh-Taylor instability. The first is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 150 publications
(186 reference statements)
0
31
0
Order By: Relevance
“…We have discussed the role that mass plays in the global evolution and eruption of flux ropes, suggesting that it depends on four main parameters; the strength of the surface field generating the background potential field, how much mass is loaded into a flux rope, how much mass drains during its evolution, and when along a flux rope's equilibrium curve the mass drains. The effect of the local evolution of plasma within prominences is not discussed in this manuscript, i.e., the mass-draining that is studied here differs from the massloss due to the Rayleigh-Taylor instability (RTI) that has been studied extensively in both observations and simulations (e.g., Hillier et al 2012;Xia & Keppens 2016;Hillier 2018). In addition, Kaneko & Yokoyama (2018) pointed out that, in their case, the mass-loss from the prominence due to RTI was balanced by new condensations into the prominence.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…We have discussed the role that mass plays in the global evolution and eruption of flux ropes, suggesting that it depends on four main parameters; the strength of the surface field generating the background potential field, how much mass is loaded into a flux rope, how much mass drains during its evolution, and when along a flux rope's equilibrium curve the mass drains. The effect of the local evolution of plasma within prominences is not discussed in this manuscript, i.e., the mass-draining that is studied here differs from the massloss due to the Rayleigh-Taylor instability (RTI) that has been studied extensively in both observations and simulations (e.g., Hillier et al 2012;Xia & Keppens 2016;Hillier 2018). In addition, Kaneko & Yokoyama (2018) pointed out that, in their case, the mass-loss from the prominence due to RTI was balanced by new condensations into the prominence.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…2014). Further discussion of models of vertical flows in prominences, including a thorough review of prominence RT instability studies, can be found in Hillier (2018).…”
Section: Adding Flesh and Blood To The Skeleton: Incorporating Dynamimentioning
confidence: 99%
“…The Rayleigh-Taylor instability (RTI) is an important instability in many astrophysical and laboratory systems, such as supernova explosions (Hachisu et al 1992;Hester et al 1996;Porth et al 2014), solar prominences (Berger et al 2010;Ryutova et al 2010;Terradas et al 2015;Hillier 2018), and inertial confinement fusion (Takabe et al 1985;Betti et al 1998). RTI occurs when a heavy fluid is initially on top of a light fluid.…”
Section: Introductionmentioning
confidence: 99%